Factors affecting the soilid waste management in Iloilo and Bacolod Cities - Baldevia, Romeo
The research study was conducted in support to the solid waste management of the cities of Iloilo and Bacolod. Using descriptive-analytical approach through primary and secondary data. The study generally aimed to determine the factors affecting the solid waste management in Iloilo and Bacolod cities. Specifically, it aimed to: 1) compare the Solid Waste ManagementProgram of the two cities and analyze their planning, implementation, monitoring and evaluation systems; 2) determine the key players, their leadership styles, and extent of their cooperation in planning, implementation, monitoring and evaluation; 3) enumerate the existing related local policies and ordinances and analyze their enforcement; and 4) identifythe major problems and constraints in planning, implementation and monitoring and evaluation and come up with appropriate recommendations. Bacolod City is ahead compared to Iloilo City in Solid Waste Management considering the systems, capability of players and the necessary resources. Both LGUs employed democratic style in planning. However,participatory processes were relatively not applied in the implementation and monitoring and evaluation. While this observation was seen less intensely in Bacolod, this was noted more in Iloilo. For all the three phases of the program, involvement were generally limited to members of task force from the LGU, government agencies. NGO with minimal participation of thecommunities especially in Iloilo. For both cities, local policies and ordinances on SWM were existing. However, the enforcement of such was not so intensive. This observation was observed more in Iloilo than in Bacolod. Major problems noted for both cities, were the lack of public awareness on the solid wastes problem and lack of participation of communities especially in the implementation and monitoring and evaluation. Although heavier weight of such problems can be applied more in Iloilo than in Bacolod. Factors affecting the Solid Waste management included: 1) extent of involvement of the different sectors in the formulation and implementation; 2) regularly of the collection and disposal of solid wastes during the implementation phase; 3) existence and strict enforcement of policies and ordinances; and 4) leadership style of local chief executive. Recommendations for LGUs can be 1) intensify public awareness and information campaign on SWM; 2) Provide capability building for players; 3) Continuously access the necessary information, technology and funding to enhance SWM; 4) Encourage democratic leadership through consultation and multi-sectoral involvement throughout the three phases of the program; 5) Review, popularize intensively and enforce strictly the policies and ordinances; and 6) Provision of necessary incentives to deserving players and communities.